2018
DOI: 10.2302/kjm.2018-0004-oa
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Characteristics, and Long-term Outcome of the Dilated Phase of Hypertrophic Cardiomyopathy

Abstract: Some patients with hypertrophic cardiomyopathy (HCM) develop systolic dysfunction, called the dilated phase of HCM (d-HCM), which is associated with increased morbidity and mortality. We conducted a retrospective study using an HCM database to clarify the incidence, clinical characteristics, and longterm outcomes of d-HCM. We analyzed an HCM cohort consisting of 434 patients (273 with apical HCM and 161 with non-apical HCM; 18 had obstructive HCM, 16 had dilated HCM, and 127 had other HCM) diagnosed by echocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although the time course of LV remodelling is heterogeneous, LV remodelling often occurs gradually over the years 15,16 . Previous studies have shown that AF and end‐stage HCM are associated with worse clinical outcomes, 13,17–20 and 74% of the patients with AF and 86% of the patients with end‐stage HCM in the present study suffered from HCM‐related adverse events. Based on these facts, it is expected that the longer the follow‐up period is, the higher will be the frequency of development of AF and end‐stage HCM.…”
Section: Discussionmentioning
confidence: 50%
“…Although the time course of LV remodelling is heterogeneous, LV remodelling often occurs gradually over the years 15,16 . Previous studies have shown that AF and end‐stage HCM are associated with worse clinical outcomes, 13,17–20 and 74% of the patients with AF and 86% of the patients with end‐stage HCM in the present study suffered from HCM‐related adverse events. Based on these facts, it is expected that the longer the follow‐up period is, the higher will be the frequency of development of AF and end‐stage HCM.…”
Section: Discussionmentioning
confidence: 50%
“…LV performance at baseline is one of the predictors of DHCM development [6]. LVDs were the most sensitive echocardiographic parameter, reflecting LV contraction and LV cavity enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…PTSMA is a septal reduction therapy for severe HOCM; however, many patients who are not candidates for surgical myectomy now receive this catheter-based procedure [8,9,22]. The long-term impact of PTSMA on LV contraction, particularly LV development, has not been thoroughly investigated because most previous studies excluded patients receiving septal reduction therapy from DHCM risk analyses [4][5][6]. The present study did not exclude patients with PTSMA because they represented one-fourth of the total patient population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations